A study on clinical profile of neonatal seizures in newborn babies born in Government Mohan Kumara Mangalam Medical College Hospital, India - S., Amudhadevi; P., Kanchana (International Journal of Contemporary Pediatrics, 2018)
Background: Seizures represent the most distinctive signal of neurological disease in the newborn period. The convulsive phenomena are the most frequent of the overt manifestations of neonatal neurological disorders. This study was aimed at providing a clear picture regarding the epidemiology, etiology, onset, types and mortality of neonatal convulsions in our hospital. This study was carried to assess the incidence, types of Neonatal convulsions, etiology, time of onset and its relationship with the etiology and to determine the mortality associated with neonatal convulsions. Methods: This study was carried out in Government Mohan Kumaramangalam Medical College Hospital in June 2016 - May 2017.The Study Population is Newborn babies born in our hospital and admitted in Neonatal Intensive Care Unit. Babies born in other hospitals or at home with neonatal convulsions were excluded from the study. A detailed history was elicited for all recruited babies and was thoroughly examined. The baby’s clinical progression was closely monitored, and relevant investigations done. Data were entered in Microsoft Excel and analyzed in SPSS version 12. Results: There were 1385 neonatal cases admitted in the newborn ward in Govt. Mohan Kumaramangalam Medical College Hospital, Salem during the period of 12 months from June 2016 to May 2017. Of these, 104 neonates had convulsions. There were 4102 total live births in this period for 12 months from June 2010 to May 2011. Of these, 104 neonates had convulsions. So, the incidence of neonatal convulsions is 2.5%. Conclusions: Since birth asphyxia is the commonest cause of neonatal convulsions, improvement in antenatal, perinatal care with early identification of high-risk mothers will reduce the incidence of birth asphyxia and thereby reduce the incidence of neonatal convulsions. Subtle seizures are the commonest type of clinical seizures; therefore, careful observation of at risk newborns is necessary.